2006
DOI: 10.1136/jmg.2006.041467
|View full text |Cite
|
Sign up to set email alerts
|

CDKL5 mutations cause infantile spasms, early onset seizures, and severe mental retardation in female patients

Abstract: The spectrum of the epileptic seizure disorder, and associated EEG changes, in those with CDKL5 mutations is broader than previously reported. CDKL5 mutations are a significant cause of infantile spasms and early epileptic seizures in female patients, and of a later intractable seizure disorder, irrespective of whether they have suspected Rett syndrome. Analysis should be considered in these patients in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
164
4
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(186 citation statements)
references
References 22 publications
14
164
4
4
Order By: Relevance
“…Previous studies of the CDKL5 disorder have also reported dysmorphic features including: large deep-set eyes, strabismus, high forehead, full lips, wide mouth, widely spaced teeth and a high palate. 1,4,5,7,13,18,20,22,25,26,[28][29][30]35 Dysmorphic features have been described in other conditions presenting with early-onset encephalopathy, such as those with FOXG1 mutations and in Pitt-Hopkins syndrome (PHS). In those with FOXG1 mutations, subtle, non-specific dysmorphic features have been reported, along with severe microcephaly, which is typical of FOXG1 syndrome but not common in individuals with the CDKL5 disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of the CDKL5 disorder have also reported dysmorphic features including: large deep-set eyes, strabismus, high forehead, full lips, wide mouth, widely spaced teeth and a high palate. 1,4,5,7,13,18,20,22,25,26,[28][29][30]35 Dysmorphic features have been described in other conditions presenting with early-onset encephalopathy, such as those with FOXG1 mutations and in Pitt-Hopkins syndrome (PHS). In those with FOXG1 mutations, subtle, non-specific dysmorphic features have been reported, along with severe microcephaly, which is typical of FOXG1 syndrome but not common in individuals with the CDKL5 disorder.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5,7,13,18,20,22,25,26,[28][29][30]35 The presence of typical facial or other features could provide additional assistance in the clinical identification of individuals with a CDKL5 mutation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The gene is composed of 20 encoding exons, and so far 450 mutations in patients with CDKL5-related encephalopathy have been reported, affecting quasi-exclusively girls. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Patients with CDKL5 mutations typically present severe intellectual disability and early seizures, microcephaly in B1/3 of cases, as well as RTT-like features such as severe hypotonia, hand stereotypies and sleep disturbances. 22 Several patients having symptoms reminiscent of a CDKL5-related disease profile have had no mutation identified, in spite of the large screening strategy that is available, suggesting that other unexplored regions and/or genetic loci are involved in the disease.…”
Section: Introductionmentioning
confidence: 99%
“…RTT (MIM 312750), an X-linked dominant male lethal neurodevelopmental disorder caused by a mutation in the MECP2 gene and characterized by a wide spectrum of clinical manifestations, was also found to be associated with West syndrome (4). Mutation analysis suggests the existence of additional loci possibly involved in both ISS and RTT (3,(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%